Stable and clean co-combustion of municipal sewage sludge with solid wastes in a grate boiler: A modeling-based feasibility study. (15th November 2022) - Gu, Tianbao; Ma, Wenchao; Guo, Zhenning; Berning, Torsten; Yin, Chungen
Graphical abstract: Highlights: Co-combustion of municipal sewage sludge and MSW. In-house bed model coupled with freeboard simulation via Fluent. Impacts of blending ratios of different feedstocks. NOx formation and emission modeling. In-situ reduction of NOx by primary air supply. Abstract: Municipal sewage sludge not only has very high moisture content and low heating value but also carries lots of nitrogen, making it difficult to attain stable and clean co-combustion with municipal solid waste (MSW) in existing MSW incinerators. Blending other high-heating value solid waste as assistive fuel in co-firing of sewage sludge and MSW is considered feasible to improve the combustion stability and meanwhile maintain the disposal capacity of the incinerator. This paper numerically investigates MSW co-firing with sewage sludge and industrial solid waste in a moving-grate MSW boiler with a capacity of 750 t/d. The co-combustion stability and nitrogen oxides (NOx ) emissions are among the main concerns, different blends of the three solid wastes and under-grate primary air (PA) distributions are probed and compared. First, a validated in-house bed model, comprehensively describing the solid fuel conversion process and heat and mass transfer phenomena on moving grates, is extended to include NOx formation and employed to simulate the combustion of various blends on the grate. Then, the fuel bed model is iteratively coupled with the simulation of the freeboard of the boiler, which is performed using ANSYS Fluent. For the various blends investigated in this study, co-combusting up to 25.6 wt% sewage sludge, with about 14.4 wt% industrial solid waste and 60 wt% MSW in the existing boiler, is feasible and recommended. By properly tuning the under-grate PA distribution, the stable, efficient and clean combustion of the feedstock blend has been achieved. Compared to the original PA distribution, up to 11.54% reduction of NOx emission from the boiler is attained, because of the enhancement of nitric oxide (NO) reduction reactions with ammonia (NH3 ) and char. At last, an in-depth analysis of co-combusting the recommended blend using the new PA distribution is elaborated. This study provides a valuable reference and guideline for stable and clean co-combustion of sewage sludge and MSW in existing incinerators.